Eight-year catalog of deep short-term slow slip events at the Nankai trough based on objective detection algorithm using strain and tilt records - Yabe, Suguru; Ochi, Tadafumi; Matsumoto, Norio; Itaba, Satoshi; Kitagawa, Yuichi; Matsuzawa, Takanori (Earth, planets, and space, 2023)
In subduction zones, slip deficit monitoring along the plate interface is important for understanding the seismogenesis of megathrust earthquakes. In the last two decades, aseismic slip transients, such as slow slip events (SSEs), which are usually synchronized with tectonic tremors, have been detected in subduction zones worldwide. Frequent SSEs are particularly important for releasing slip deficits during the inter-seismic periods of megathrust earthquakes. In southwest Japan, deep short-term SSEs have been primarily monitored with strain and tilt records because the SSEs in this region are small. However, strain and tilt records are so sensitive that they record not only SSEs, but also rainfall and local groundwater movements, which temporally affect the quality of data making it difficult to apply an automated detection algorithm. Therefore, previously reported short-term SSE catalogs, based on strain and tilt records, were created by visual inspections, although they are not suitable for generating a long-term catalog. In this study, a quantitative detection algorithm was developed to detect short-term SSEs using strain and tilt records. The problem of temporally varying data quality was solved by introducing the prior probability of log-normal distributions in the fitting variance. This method was applied to an 8-year (2013–2020) dataset of strains and tilts from southwest Japan. A total of 96 events were detected, among which, 78 corresponded with SSEs previously reported by the Geological Survey of Japan (GSJ). Although the GSJ catalog contained more events with smaller magnitudes, such events were difficult to distinguish from noise using the developed method. Three of the remaining 18 events were considered SSEs that were not reported in the GSJ catalog. Others could be artifacts because there were no obvious signals in the global navigation satellite system records (with events of magnitude > 6.0). Previous studies have suggested the existence of aseismic transients deeper or shallower than regular short-term SSEs in southwest Japan. However, detection results from this study did not confirm such events. Graphical Abstract